2023
DOI: 10.1038/s41598-023-34418-y
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes with overexpressed miR 147a suppress angiogenesis and infammatory injury in an experimental model of atopic dermatitis

Abstract: Atopic dermatitis is defined as an intensely systemic inflammation among skin diseases. Exosomes derived from adipose-derived stem cells may be a novel cell-free therapeutic strategy for atopic dermatitis treatment. This study aims to elucidate the possible underlying mechanism of adipose-derived stem cells-exosomes harboring microRNA-147a in atopic dermatitis pathogenesis. BALB/c mice treated with Dermatophagoides farinae extract/2,4-dinitrochlorobenzene were defined as a mouse model of atopic dermatitis, eit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A disrupted epidermal barrier in AD is restored by the de novo synthesis of ceramides induced by the MSC-derived exosomes [44]. It has also been shown that exosomes in which miR 147a was overexpressed suppressed in ammatory injury in an AD mouse model [45].…”
Section: Discussionmentioning
confidence: 99%
“…A disrupted epidermal barrier in AD is restored by the de novo synthesis of ceramides induced by the MSC-derived exosomes [44]. It has also been shown that exosomes in which miR 147a was overexpressed suppressed in ammatory injury in an AD mouse model [45].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, deep RNA sequencing analysis of skin lesions demonstrated that ADSC-exos normalized the expression of genes altered during AD pathogenesis, which involved skin barrier, lipid metabolism, cell cycle, and inflammatory response. Shi et alreported that miR-147a-overexpressing ADSC-exos inhibited inflammatory response, cell apoptosis, and angiogenesis in the DNCB-induced AD mouse model via targeting VEGF-A and MEF2A-TSLP axis 41 . In addition, exosomes based on skin component cells or other stem cells, such as dermal fibroblasts and iPSC-derived MSCs (iMSCs), possess outstanding advantages in modulating inflammation and promoting tissue regeneration and repair and are expected to be candidates for AD therapy.…”
Section: Exosomes In Inflammatory Skin Diseasementioning
confidence: 99%
“…For AD mice induced by Dermatophagoides farinae extract and 2,4-dinitrochlorobenzene, Shi et al. [ 92 ] found that miR-147a levels decreased markedly in the serum and skin lesions, meanwhile thymic stromal lymphopoietin (TSLP, a cytokine involved in the angiogenic phenotype and AD pathogenesis) and VEGFA (a key regulator of angiogenesis) increased markedly. These observations revealed that miR-147a correlated negatively with the expression levels of VEGFA and TSLP in AD lesions.…”
Section: Skin Diseasesmentioning
confidence: 99%